Trastorno de simulación en niños y su influencia en el funcionamiento socioafectivo de un paciente - Mero Cedeño, Selena Jamileth (2019)
In the present research work a case study is developed, in which a psychotherapeutic plan is proposed, the same one that is oriented under cognitive-behavioral techniques, developed for the therapeutic intervention of a patient with 12 years, the same as Through a psychodiagnostic process, it was diagnosed with simulation, while pre-professional practices were carried out in the Cantonal Board for the Protection of Rights of the City of Babahoyo, impacting on socio-affective functioning. In the development of the case study, signs and symptoms manifested by the patient and her clinically significant discomfort will also be described, in addition the content is defined through theoretical bases, where simulation detection is taken into account, its definition as such, the family as an important role in the development of the child, socio-affective development and recounts the importance of family support in the treatment of the patient, describes in detail the intervention and techniques used